2019
DOI: 10.1111/clr.13413
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography evaluation of staged lateral ridge augmentation using platelet‐rich fibrin or resorbable collagen membranes in a randomized controlled clinical trial

Abstract: Objectives To evaluate the volumetric changes following lateral alveolar ridge augmentation using autogenous bone graft covered by either a platelet‐rich fibrin membrane (test group) or an inorganic bovine bone substitute and a resorbable collagen barrier membrane (control group). Material and methods A total of 27 partially edentulous patients (test n = 14, control n = 13) with the indication for lateral bone block augmentation were included in this randomized, controlled clinical trial. Cone beam computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
1
26
0
7
Order By: Relevance
“…As a result, many studies have reported successful results with a mixture of an adequate scaffold and bone growth factors such as recombinant human platelet-derived growth factor (rhPDGF) and recombinant human bone morphogenetic protein-2 (rhBMP-2) 13,14 . Recently, several studies reported good bone healing after bone grafts with platelet rich plasma (PRP) or platelet rich fibrin (PRF) which could be obtained and prepared from the venous blood of patients 15 . Jeon et al 16 reported a 3.3 mm increase through vertical ridge augmentation using β-tricalcium phosphate with PRP.…”
Section: Bone Growth Factorsmentioning
confidence: 99%
“…As a result, many studies have reported successful results with a mixture of an adequate scaffold and bone growth factors such as recombinant human platelet-derived growth factor (rhPDGF) and recombinant human bone morphogenetic protein-2 (rhBMP-2) 13,14 . Recently, several studies reported good bone healing after bone grafts with platelet rich plasma (PRP) or platelet rich fibrin (PRF) which could be obtained and prepared from the venous blood of patients 15 . Jeon et al 16 reported a 3.3 mm increase through vertical ridge augmentation using β-tricalcium phosphate with PRP.…”
Section: Bone Growth Factorsmentioning
confidence: 99%
“…However, two-dimensional linear clinical or radiographic measurements were used in all the included studies of the present systematic review revealing a non-significant tendency to increased gain in alveolar ridge width and diminish postoperative resorption with the use of barrier membrane coverage [18,[33][34][35]. High degree of reliability, accuracy and reproducibility in quantifying volumetric changes of the augmented area following LARA with the use of three-dimensional computer software have previous been reported in clinical and experimental studies [44,45]. A previous study using threedimensional volumetric assessment of the augmented area following LARA with an autogenous bone block graft alone from the iliac crest without barrier membrane coverage revealed a volume reduction of the augmented area by 78%, whereas two-dimensional linear measurements disclosed an alveolar ridge reduction from 11,2 mm to 5,6 mm corresponding to 50%, after two years [46].…”
Section: Discussionmentioning
confidence: 93%
“…At the final follow-up, both groups demonstrated favourable peri-implant marginal bone levels, although the PRF group revealed a 0.43 mm (p = 0.03) higher peri-implant marginal bone level than the control group, meaning that the bone level was higher around the implant for the test group. This difference may be caused by a higher number of incisor implants in the control group (Table 1), since a more pronounced bone resorption rate in the anterior region compared to the posterior region following bone block augmentation has previously been described [26]. One patient in the PRF group demonstrated bone resorption around the implant at the abutment operation of more than 1 mm, but the marginal peri-implant bone level of that implant was stable both when the impression was taken and at the final follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…The volumetric changes of the augmented bone [26], the histological composition of the augmented bone [27] and pain after the primary bone augmentation procedure [28] were previously described in detail.…”
Section: Methodsmentioning
confidence: 99%